The significance of the additional verb in Al-shakshakiah sermon of Imam Ali (peace be upon him) (Journal of the College of Education for Women, 2019)
The contextual clues researcher guide to determine the meaning of the word is likely to several meanings, was contextual clues Dalili in determining the meanings morphological acts whipped in a sermon Alhqhqih.And meanings are endless on the contrary language words used to express these meanings, we find that one word may be used to express more than one meaning, leading to the phenomenon of semantic possibility.So it was inevitable that contain language text on the signs designate the reader and listener and researcher to identify the intended meaning, and these signs are contextual clues in the text.Actual formulas whipped features from other formulas morphological Pkthertha frequent use and the large number of meanings mentioned by scientists using a formula for each of them, so is the need to contextual clues that help in determining the meaning of them.Therefore, the context of the significant impact in determining the meaning of the actual morphological formula, and the material derivative of great importance in determining the intended meaning.As well as the wife of a Bedouin location of the word and the presumption of infringement necessary and important clues in determining the significance act more.Context may be a words presents to the intended meaning and eliminate the possibility of semantic, and the remaining material is the strongest presumption clues.